The water metabolism in cesareada, their relationship with labor, duration of surgery and postpartum complications - Keymer F., Eduardo (2015)
In previous work we have seen the differences in relation to water metabolism between a current operation, outside of pregnancy and the Caesarean operation; this time we will study the influence it may have the duration of the operation, the circumstances of work delivery and post-operative complications on the behavior of water metabolism.